2005
DOI: 10.2174/157341105774573956
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Screening by Saturation-Transfer Difference (STD) NMR Spectroscopy

Abstract: NMR based methods to screen for high-affinity ligands have become an indispensable tool for designing rationalized drugs, as these offer a combination of good experimental design of the screening process and data interpretation methods, which together provide unprecedented information on the complex nature of protein-ligand interactions. These methods rely on measuring direct changes in the spectral parameters, that are often simpler than the complex experimental procedures used to study structure and dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…The amplification factor ( A STD ) is obtained by multiplying the relative STD effect of a given signal (the intensity of a signal in the difference spectrum divided by its intensity in the reference spectrum, I STD / I 0 ) with the molar ratio of ligand relative to the protein, [odorant]/[OR]. The concentration of OR was taken to be 13 nmol/L, and the concentration of odorant was taken to be the average of the ERETIC (electronic reference to access in vivo concentrations) values for the samples with and without the metal salts. Previously, we have shown that for the three independent experiments with TBM, CuCl 2 , and MOR244-3, I STD / I O was equal to 0.002 with a relative standard deviation of 13%.…”
Section: Resultsmentioning
confidence: 99%
“…The amplification factor ( A STD ) is obtained by multiplying the relative STD effect of a given signal (the intensity of a signal in the difference spectrum divided by its intensity in the reference spectrum, I STD / I 0 ) with the molar ratio of ligand relative to the protein, [odorant]/[OR]. The concentration of OR was taken to be 13 nmol/L, and the concentration of odorant was taken to be the average of the ERETIC (electronic reference to access in vivo concentrations) values for the samples with and without the metal salts. Previously, we have shown that for the three independent experiments with TBM, CuCl 2 , and MOR244-3, I STD / I O was equal to 0.002 with a relative standard deviation of 13%.…”
Section: Resultsmentioning
confidence: 99%
“…To-date, only a closed-216 loop structure of hPIV-3 HN has been observed in complex with zanamivir ( 3 ) 25 38 . Since we observe an increase in STD-NMR signals for zanamivir ( 3 ) in the presence of suramin ( 7 ) and hPIV-3 HN, it suggests that a faster exchange of zanamivir ( 3 ) from bound- to free-form occurs 41 . A possible explanation of this outcome is that suramin ( 7 ) induces the 216 loop to open enabling this faster exchange.…”
Section: Discussionmentioning
confidence: 73%
“…In order to understand the molecular‐level interactions of the active compounds with tubulin, those were analyzed by the NMR saturation transfer difference experiment (NMR‐STD). This pulse sequence allows the identification of the hydrogen atoms of the ligand that participate in interactions with tubulin (Krishnan, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrated that all signals in the STD spectra in the presence of the protein correspond to the hydrogens from the ligand structure that were involved in the interaction with the protein. These protons suffered interference of protein magnetization, induced by saturation NMR radio frequency pulse-a process that allows the characterization of groupspecific epitopes of the ligands (Krishnan, 2005;Monaco et al, 2017). Compounds 1, 17, and 26 showed interaction with the protein in the STD spectra (Figures S8 and S9).…”
Section: Nmr Interaction Study Of the Selected Compounds Against Tubulinmentioning
confidence: 99%